2016
DOI: 10.1002/ejic.201600628
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Activity and Mechanism of Co‐Catalysts Used in Combinational Catalysts for Aerobic Oxidation

Abstract: (2,2,6,6‐Tetramethylpiperidin‐1‐yl)oxyl (TEMPO) was immobilized on crosslinked polystyrene (CPS) microspheres by polymer reaction to obtain microspheres of the heterogeneous catalyst TEMPO/CPS. TEMPO/CPS microspheres in combination with different transition metal salts were used in the aerobic oxidation of 1‐phenylethanol. This work focuses on the catalytic activities and mechanisms of various co‐catalysts, and the different behavior of these co‐catalysts is explained for the first time with the theory of redo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…These results clearly showed that employing redox-active metals such as Fe and Cu had a better effect on the reaction outcome in CH 3 CN. On the basis of the results of this experiment and the previous reports, 43 a plausible reaction pathway is illustrated in Scheme 2. In this proposed mechanism, by the oxidation action of Fe III or Cu II , TEMPO is transformed into a nitrogen carbonyl cation by a single-electron oxidation, and this cation extracts a hydrogen atom from HMF to transform it to DFF.…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…These results clearly showed that employing redox-active metals such as Fe and Cu had a better effect on the reaction outcome in CH 3 CN. On the basis of the results of this experiment and the previous reports, 43 a plausible reaction pathway is illustrated in Scheme 2. In this proposed mechanism, by the oxidation action of Fe III or Cu II , TEMPO is transformed into a nitrogen carbonyl cation by a single-electron oxidation, and this cation extracts a hydrogen atom from HMF to transform it to DFF.…”
Section: Resultssupporting
confidence: 64%
“…These results clearly showed that employing redoxactive metals such as Fe and Cu had a better effect on the reaction outcome in CH 3 CN. On the basis of the results of this experiment and the previous reports, 43 a plausible reaction pathway is illustrated in Scheme 2. In this proposed − ion is reduced to the NO 2 − ion.…”
Section: ■ Results and Discussionmentioning
confidence: 68%
“…In contrast, at 60 °C, the reaction rate improved greatly with the O 2 balloon, and the reaction was completed in 20 min. The proposed catalytic cycle for aerobic oxidation is shown in Scheme 1 [ 40 , 46 47 ]. At room temperature, the solubility of O 2 in the reaction solution is relatively high, and the catalytic cycle A, which is associated with the solubility of O 2 , is not the rate-determining step.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, at 60°C, the reaction rate improved greatly with the O2 balloon, and the reaction was completed in 20 min. The proposed catalytic cycle for aerobic oxidation is shown in Scheme 1 [35,41,42]. At room temperature, the solubility of O2 in the reaction solution is relatively high, and the catalytic cycle A, which is associated with the solubility of O2, is not the rate-determining step.…”
Section: Reaction Optimization For Aerobic Oxidation Under Batch Cond...mentioning
confidence: 99%